Phenotyping and combining ability analysis of sorghum [sorghum bicolor (l) Moench] genotypes in dryland environments - Temesgen Begna; Techale Birhan; Taye Tadesse (Discover Sustainability)
Abstract Sorghum has profound role in ensuring food security across the globe, especially in dry lowland regions. However, substantial sorghum productivity has been curtailed by severe and prolonged drought stress due to the limitation of climate smart and superior sorghum varieties for moisture stress areas of Ethiopia. Therefore, this study was conducted to identify and develop superior sorghum genotypes through investigating gene action and combining abilities for yield and agronomic traits. In total, 42 sorghum genotypes were assessed in alpha lattice design with two replication. There was considerable differences amongst genotypes for yield and agronomic characteristics. Best performing hybrids such as P-9534 × Melkam (6.32 tha−1), B6 × ICRS-14 (5.92 tha−1) TX-623 × ICRS-14 (5.88 tha−1), P9511 × Melkam (5.78 tha−1) and P-850341 × ICRS-14 (5.57tha−1) were identified with yield advantage of 32.49%, 24%, 23%, 21% and 16.68% over the standard check (ESH-4) (4.77 tha−1) respectively. Inbred lines P-9534 and P-9505 were identified as the best general combiners for the plant height and days to flowering, while P-9501 and B5 were found to be the best general combiner parents for stay green. In terms of thousand-seed weight, the best general combiners were P-850341, MARC2, and MARC6 inbred lines. This signified the traits were principally governed by additive gene action and early generation selection was the most preferred strategies for further improvement. The hybrids P-9534 × Melkam, B6 × ICRS-14, and MARC3 × Melkam were identified as best specific combiners for grain yield, while TX-623 × ICRS-14 was the best specific combiner for panicle width, 1000-seed weight, days to flowering and days to maturity. This demonstrated non-additive gene action mainly controlled the traits and heterotic breeding strategies was advised to develop superior sorghum hybrids. Since the ratio of specific to general combining ability was more than unity for all traits except plant height, the investigation demonstrated the preponderance of non-additive gene action. In conclusion, after further investigation for stability and adaptability over years across locations, the drought-resistant and high-yielding hybrids (TX-623 × ICRS-14, MARC3 × Melkam, MARC3 × ICRS-14, P-9511 × Melkam, P-850341 × ICRS-14, P-9534 × Melkam, and B6 × ICRS-14) would be utilized commercially.